Detection of Tritrichomonas foetus by PCR and DNA Enzyme Immunoassay Based on rRNA Gene Unit Sequences - Felleisen, Richard S. J. (American Society for Microbiology, 1998)
Tritrichomonas foetus is the causative agent of bovine tritrichomonosis, a sexually transmitted disease leading to infertility and abortion. Diagnosis is hampered by putative contamination of samples with intestinal or coprophilic trichomonadid protozoa which might be mistaken for T. foetus. Therefore, we developed a PCR test optimized for applicability in routine diagnosis. Amplification is based upon primers TFR3 and TFR4 directed to the rRNA gene units of T. foetus. In order to avoid potential carryover contamination by products of previous amplification reactions, conditions were adapted to the use of the uracil DNA glycosylase system. Furthermore, documentation and interpretation of results were facilitated by including a DNA enzyme immunoassay for the detection of amplification products. Specificity was confirmed with genomic material from different related trichomonadid protozoa. The high sensitivity of the test allowed the detection of a single T. foetus organism in diagnostic culture medium or about 50 parasites per ml of preputial washing fluid. The present methods are thus proposed as (i) confirmatory tests for microscopic diagnosis following diagnostic in vitro cultivation and (ii) a direct T. foetus screening test with diagnostic samples.